2017
DOI: 10.3171/2016.11.spine16537
|View full text |Cite
|
Sign up to set email alerts
|

A systematic multidisciplinary initiative for reducing the risk of complications in adult scoliosis surgery

Abstract: OBJECTIVESystematic multidisciplinary approaches to improving quality and safety in complex surgical care have shown promise. Complication rates from complex spine surgery range from 10% to 90% for all surgeries, and the overall mortality rate is 1%–4%. These rates suggest the need for improved perioperative complex spine surgery processes designed to minimize risk and improve quality.METHODSThe Group Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 23 publications
0
36
0
1
Order By: Relevance
“…Several efforts have been published to develop more comprehensive preoperative evaluation protocols, including multi-disciplinary conferences and careful anesthetic preparations prior to complex spine operations. 48 , 49 These team approaches to complex spine operations have been shown to reduce reoperation, wound infection, deep venous thromboembolism, and other perioperative complications. 50 Spinal surgeons and insurance payers are increasingly focused on optimizing modifiable patient risk factors prior to surgery, such as smoking, osteoporotic bone density, and elevated hemoglobin A1C.…”
Section: Resultsmentioning
confidence: 99%
“…Several efforts have been published to develop more comprehensive preoperative evaluation protocols, including multi-disciplinary conferences and careful anesthetic preparations prior to complex spine operations. 48 , 49 These team approaches to complex spine operations have been shown to reduce reoperation, wound infection, deep venous thromboembolism, and other perioperative complications. 50 Spinal surgeons and insurance payers are increasingly focused on optimizing modifiable patient risk factors prior to surgery, such as smoking, osteoporotic bone density, and elevated hemoglobin A1C.…”
Section: Resultsmentioning
confidence: 99%
“…In complex ASD surgeries, the implementation of risk reduction protocols, such as the Seattle Spine Team Protocol, have accounted for decreased complication rates [48,49]. Sethi et al [49] reported that the combined use of a multidisciplinary spinal surgery conference, a patient education course, dual operating surgeons, a dedicated complex spine anesthesia team, and enhanced intraoperative monitoring of laboratory measurements and vitals, led to a 51% decline in the 30-day complication rate for complex ASD surgery patients. The use of frailty index scores and the consequent estimation of mortality and complication rate could provide clinically pertinent information to the multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary preoperative conference, dual attending surgeons, and a detailed protocol for coagulopathy/blood loss in the operating room are part of the Seattle spine team approach. 48,93 The presence of dual attending surgeons can decrease operative time. Utilization of the anesthesia team to implement a transfusion protocol reduced perioperative blood loss and coagulopathy.…”
Section: Surgical Risk Assessmentmentioning
confidence: 99%